2020
DOI: 10.3390/su12176728
|View full text |Cite
|
Sign up to set email alerts
|

High Academic Self-Efficacy and Dispositional Empathy in Future Teachers

Abstract: High perceived academic self-efficacy influences both subject performance and emotions of the subject. In turn, dispositional empathy implies a social and emotional adaptability towards the subject itself and those around them. This study aimed to analyze the differences in the mean dispositional empathy factors (i.e., perspective taking, fantasy, empathic concern and personal distress) between future teachers with high and low perceived academic self-efficacy, as well as the predictive capacity of disposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Second, consistent with our hypotheses, mindfulness and counselor's self-efficacy independently mediated the self-oriented empathy-CF linkage. In line with previous studies, we found that self-oriented empathy could negatively predict dispositional mindfulness (Baer, 2004;Dekeyser et al, 2008;Fuochi and Voci, 2020) and context-specific self-efficacy (Aparicio-Flores et al, 2020). We also found that low levels of mindfulness and contextspecific self-efficacy were associated with a high level of CF, which is consistent with previous studies (Olson et al, 2015;Shoji et al, 2015;Brown et al, 2017;Kind et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Second, consistent with our hypotheses, mindfulness and counselor's self-efficacy independently mediated the self-oriented empathy-CF linkage. In line with previous studies, we found that self-oriented empathy could negatively predict dispositional mindfulness (Baer, 2004;Dekeyser et al, 2008;Fuochi and Voci, 2020) and context-specific self-efficacy (Aparicio-Flores et al, 2020). We also found that low levels of mindfulness and contextspecific self-efficacy were associated with a high level of CF, which is consistent with previous studies (Olson et al, 2015;Shoji et al, 2015;Brown et al, 2017;Kind et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Although feelings of empathy are considered transitory states, many researchers believe that some people are more likely to experience these states than others or experience these states to a greater extent (Lishner et al, 2017). Teachers' selfefficacy, or their belief in their ability to handle teachingrelated tasks, was found to contribute to empathy in teachers (Aparicio-Flores et al, 2020;Goroshit & Hen, 2016). This relationship was also demonstrated in an earlier study -more specifically, higher levels of perspective-taking (cognitive empathy) were associated with higher self-efficacy (Davis, 1983).…”
Section: Predictors Of Empathysupporting
confidence: 65%
“…The aim of this study was to empirically investigate the condition(s) under which an individual with a positive attitude towards others decides to create a social venture. Based on prior literature (Aparicio-Flores et al , 2020; Bacq and Alt, 2018; Pang et al , 2022; Tiwari et al , 2022 Zeng and Chen,2022), we proposed that attitudes towards others, such as empathy and moral obligation, predicts SEI through social entrepreneurial self-efficacy and perceived social support. We found support for our mediation model across two different samples, one from a frontier economy and the other from an emerging economy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the existing literature suggests that an others-oriented attitude most accurately predicts a behaviour through individual and contextual factors, such as selfefficacy and perceived social support (Aparicio-Flores et al, 2020;Domene, 2012;Pang et al, 2022;Zeng and Chen, 2022). More specifically, empathy acts as an antecedent of (social entrepreneurial) self-efficacy, thus influencing outcome expectations and SEI through social entrepreneurial self-efficacy (Aparicio-Flores et al, 2020;Bacq and Alt, 2018;Ip et al, 2021). It also indirectly shapes one's prosocial behaviour through perceived social support (Fu et al, 2022).…”
Section: Empathy and Social Entrepreneurial Intentionmentioning
confidence: 95%